Deposition of onco-histone H3.3-G34W leads to DNA repair deficiency and activates cGAS/STING-mediated immune responses - Mancarella, Daniela; Ellinghaus, Henrik; Sigismondo, Gianluca; Veselinov, Olivera; Kühn, Alexander; Goyal, Ashish; Hartmann, Mark; Fellenberg, Jörg; Krijgsveld, Jeroen; Plass, Christoph; Popanda, Odilia; Schmezer, Peter; et al. (International journal of cancer, 2024)
Mutations in histone H3.3-encoding genes causing mutant histone tails are associated with specific cancers such as pediatric glioblastomas (H3.3-G34R/V) and giant cell tumor of the bone (H3.3-G34W). The mechanisms by which these mutations promote malignancy are not completely understood. Here we show that cells expressing H3.3-G34W exhibit DNA double-strand breaks (DSBs) repair defects and increased cellular sensitivity to ionizing radiation (IR). Mechanistically, H3.3-G34W can be deposited to damaged chromatin, but in contrast to wild-type H3.3, does not interact with non-homologous end-joining (NHEJ) key effectors KU70/80 and XRCC4 leading to NHEJ deficiency. Together with defective cell cycle checkpoints reported previously, this DNA repair deficiency in H3.3-G34W cells led to accumulation of micronuclei and cytosolic DNA following IR, which subsequently led to activation of the cyclic GMP-AMP synthase/stimulator of interferon genes (cGAS/STING) pathway, thereby inducing release of immune-stimulatory cytokines. These findings suggest a potential for radiotherapy for tumors expressing H3.3-G34W, which can be further improved by combination with STING agonists to induce immune-mediated therapeutic efficacy.
Gesehen am 22.07.2024